2022
DOI: 10.1021/acs.inorgchem.2c01840
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of a Ru Catalyst Containing Single Atoms and Nanoparticles on Nitrogen-Doped Carbon with Superior Hydrogen Evolution Reaction Activity in a Wide pH Range

Abstract: Ruthenium, which is relatively cheap in precious metals, has become a popular alternative for a hydrogen evolution reaction (HER) catalyst because of its corrosion resistance and appropriate metal–H bond strength. Convenient synthesis and active site regulation are conducive to stimulating the excellent catalytic performance of Ru as much as possible. Herein, using the mature mesoporous nitrogen-doped carbon material as the support, the catalytic materials containing both single atom Ru and Ru nanoparticles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…In particular, the mass activity was also calculated as an important indicator for evaluating the noble metal HER catalyst. As displayed in Figure S14, the Ru NPs/NC-900 catalyst exhibited obviously higher mass activity than that of the commercial 20 wt % Pt/C catalyst, indicating the superior practical application potential of Ru NPs/NC-900 . In addition to the HER activity, stability is another key factor to evaluate an electrocatalyst.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the mass activity was also calculated as an important indicator for evaluating the noble metal HER catalyst. As displayed in Figure S14, the Ru NPs/NC-900 catalyst exhibited obviously higher mass activity than that of the commercial 20 wt % Pt/C catalyst, indicating the superior practical application potential of Ru NPs/NC-900 . In addition to the HER activity, stability is another key factor to evaluate an electrocatalyst.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As displayed in Figure S14, the Ru NPs/NC-900 catalyst exhibited obviously higher mass activity than that of the commercial 20 wt % Pt/C catalyst, indicating the superior practical application potential of Ru NPs/NC-900. 50 In addition to the HER activity, stability is another key factor to evaluate an electrocatalyst. In Figures 3c and S15, Ru NPs/ NC-900 displayed no appreciable activity degradation after the long-term stability test.…”
Section: Electrocatalytic Activity and In Situ X-ray Absorption Spect...mentioning
confidence: 99%
“…The charge relaxation time is decreased from 0.05 to 0.03 s after activation, suggesting the improved HER transfer kinetics. Interestingly, we found that the charge relaxation time of our sample is even shorter than the state-of-the-art commercial Pt/C catalysts (0.62 s) and Ru single-atom catalysts (0.08 s) 66 . It is interesting to see a rapid relaxation process (10 −4 s) in the high-frequency (10 3 –10 4 Hz) regime, which is two orders of magnitude lower than the interfacial charge transfer process.…”
Section: Resultsmentioning
confidence: 63%
“…Moreover, the N 1s binding energy of Ru/CNT@CN is divided into four independent peaks, including pyridinic N (398.7 eV), pyrrolic N (400.0 eV), Ru−N (401.2 eV), and graphitic N (404.5 eV) (Figure 2d). 30,35 These data further prove the electronic transfer from Ru NCs to pyrrolic N and indicate that the Ru NCs with low surface electronic density might show high selectivity in the hydrogenation reaction of nitro compounds. 2.2.…”
Section: Resultsmentioning
confidence: 61%